PENGGUNAAN TEKNIK MERONCE PADA PEMBELAJARAN SENI BUDAYA DAN PRAKARYA - Ikrom, Fadhli Dzil; Rahayu, Maulina (Journal of Professional Elementary Education, 2025)
This research aims to understand the use of meronce techniques in learning Arts, Culture and Crafts. In this research, the method chosen is a literature review as a guide in preparing writing. The concepts studied are described according to research variables, with a focus on two sources of information: primary sources consisting of thesis materials and research reports, and secondary sources in the form of educational research journals. One form of activity that can help develop children's fine motor skills is bouncing activities. This study aims to investigate the effect of ronce activities on the fine motor development of children aged 5-6 years. The method used was an experiment with a one group pre-test and post-test design. The results of the research show that there is a positive influence of ronce activities on the fine motor development of children aged 5-6 years. Therefore, it is recommended that ronce activities be carried out regularly for children of this age, in order to improve their fine motor development.